Physical Activity Level and Gestational Diabetes Mellitus among Pregnant Women Visiting Public Healthcare Facilities - Mohd Asri, Anis Haneesa; Mohammad Nazari, Muhammad Hazeem Na’immullah; Abdul Hamid, Syahrul Bariah (Jurnal Gizi dan Pangan, 2025)
The aim of this study is to assess the prevalence of physical activity among pregnant women during early pregnancy, which is during their first trimester, and to investigate the determinants of Gestational Diabetes Mellitus (GDM) related to sociodemographic and physical activity level. This cross-sectional study focused on pregnant women aged between 18–45 in their second or third trimester of pregnancy and visiting selected public healthcare facilities. Questionnaires including sociodemographic, anthropometric, medical history, and the Pregnancy Physical Activity Questionnaire (PPAQ) were distributed. About 123 mothers were enrolled in this study. About 86.2% of them are physically active during early pregnancy, whereas just 13.8% are physically inactive. There was no statistically significant difference between pregnant mothers with and without GDM in physical activity level. Women aged 30 and older are three times more likely to acquire GDM (AOR=3.363, 95% CI: 1.314‒8.609), while women with a pre-pregnancy BMI of overweight or obese are 2.622 times more likely to develop GDM (AOR=2.622, 95% CI: 1.170‒5.875). In conclusion, even though both pregnant women with and without GDM have a high level of physical activity, the length of time spent in sedentary activities is notable. However, no significant relationship was observed between physical activity and GDM development, as most individuals were found to be following the suggested physical activity duration, yet advanced age and obese pre-pregnancy BMI were found to be determinants of the GDM occurrence.